The effect of nano selenium foliar application on some secondary metabolites of Hypericum perforatum L. - Mahmonir Rezaei Nazari; Vahid Abdossi; Fariba Zamani Hargalani; Kambiz Larijani (Institue of Medicinal Plants, ACECR, 2022)
Background: Hypericum perforatum L. belongs to the Hypericaceae family has been considered due to its medicinal properties. The use of nanofertilizers can improve the yield and medicinal value of plants. Selenium has a protective role and a positive effect on the quantitative and qualitative characteristics of plants. Objective: Due to the importance of secondary metabolites of this plant and its economic value as well as the use of environmentally friendly fertilizers, this study was performed in the greenhouse of Shariati University of Tehran in 2019 in the form of a randomized complete block design with 3 replications. Methods: Nano selenium and selenate selenium were applied at concentrations of 6, 8, 10 and 12 mg/L in the rosette stage. Essential oil components were identified using gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS). Results: The results showed that the highest amount of α-pinene with 22 % was obtained in the control treatment and also in the treatments of 6 and 8 mg/L sodium selenate with 21.6 % and 19.5 %. The maximum content of n-octane was in the foliar application of 12 mg/L nano selenium with 16 %. Maximum nonane was obtained with 18 % and 16 % of 12 and 10 mg/L sodium selenate, respectively. Conclusion: Sodium selenate treatments are recommended if the purpose is producing normal hydrocarbon compounds.